Cancer-related Knowledge, Attitudes and Behaviors within the Latino Faith Community in South Los Angeles - Lucas-Wright, Aziza (Ethn Dis, 2019)
OBJECTIVES: The goal of this study was to establish relationships with Latino churches in South Los Angeles and to collect data from parishioners regarding their access to care, cancer risk factors, and cancer-related knowledge, attitudes and screening. METHODS: In 2014, we approached five Latino churches. All allowed us to describe the study and to consent potential respondents at a designated time during the church service. RESULTS: 398 Latino respondents (75% female) completed the survey in English (15%) or Spanish (85%). Most respondents were born in Mexico (63%). Only 56% had health insurance and 51% had a regular doctor. Based on self-reported height and weight, 33% were overweight and 51% were obese. However, only 42% of obese respondents had been told by their doctor that they were obese. Although it is well-established that obesity is a major cancer risk factor, respondents lacked knowledge about the important role of nutrition and exercise in cancer prevention. Among women, adherence to national screening guidelines was 88% for cervical cancer, 72% for breast cancer and 58% for colorectal cancer. However, they were quite willing to undergo cancer screening if recommended by a physician and reported few barriers to colorectal cancer screening. CONCLUSIONS: Our data suggest a need to focus on both primary and secondary cancer prevention by promoting healthy lifestyles to curb the obesity epidemic and by promoting colorectal cancer screening. These data will inform future interventions to promote wellness in South Los Angeles in collaboration with the Latino faith community.